A study on bus safety operation system applying IoT technology - Chul Kim, Hee (International Journal of Engineering and Technology, 2018)
Background/Objectives: It is a bus safe operation system applying IoT (Internet of Thing) technology. It is the starting point of future economic activitiessuch as past simple transportation methods and various information such as health care, wearable, IoT, We want to change the paradigm into service exchange space. Vehicle infotainment technology utilizes a bi-directional head-up display (HUD) interface technology to detect the wheel state of the steering wheel operation, which is the driver's operation behavior, and the pupil watching forward, and warns if momentary carelessness or continuous carelessness occurs, Avoid.Methods/Statistical analysis: Since the ratio of the eye area in the face area is very small, there is a possibility that the calculation time is greatly increased. In order to optimize the module, based on the analysis of the Korean face information, Thereby reducing the search time. Driver Monitoring System (DMS) developed by Toyota is an infrared camera module installed in front of the dashboard to monitor driver's eyelids and head movements during driving to determine driver's sleepiness.Findings: Based on the know-how of wireless communication-based healthcare device manufacturing technology, we can develop user-oriented products that can differentiate from the existing IoT healthcare products and develop wireless communication-based healthcare for large- We will develop a care terminal to secure marketability.Improvements/Applications: Developed commercial products focusing on the technology stabilization centered on the large transportation profession, obtained stable sensor information and obtained relatively accurate sensing information without inconvenience for long-term operation or work. Active braking assist is a fully automated control system that stops the vehicle when it detects the risk of a frontal collision. Using three radar beams installed in the vehicle, it detects up to 150m in front of the vehicle, helping to avoid the risk of a frontal collision.
Keywords: Fabric Area Network; Internet of Things; Cloud Computing; Wearable; Augmented Reality.